Dissociations in the effect of delay on object recognition: evidence for an associative model of recognition memory - Tam, Shu K.E.; Robinson, Jasper; Jennings, Dómhnall J.; Bonardi, Charlotte (American Psychological Association, 2014)
Rats were administered 3 versions of an object recognition task: In the spontaneous object recognition task (SOR) animals discriminated between a familiar object and a novel object; in the temporal order task they discriminated between 2 familiar objects, 1 of which had been presented more recently than the other; and, in the object-in-place task, they discriminated among 4 previously presented objects, 2 of which were presented in the same locations as in preexposure and 2 in different but familiar locations. In each task animals were tested at 2 delays (5 min and 2 hr) between the sample and test phases in the SOR and object-in-place task, and between the 2 sample phases in the temporal order task. Performance in the SOR was poorer with the longer delay, whereas in the temporal order task performance improved with delay. There was no effect of delay on object-in-place performance. In addition the performance of animals with neurotoxic lesions of the dorsal hippocampus was selectively impaired in the object-in-place task at the longer delay. These findings are interpreted within the framework of Wagner’s (1981) model of memory.